2016
DOI: 10.3329/ijns.v4i2.28597
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinico-pathological parameters of PPR infected goats and their response to antibiotic treatment at Panchlaish, Chittagong, Bangladesh

Abstract: The present study was conducted in the Panchlaish Upazilla Veterinary Hospital of Chittagong district during the period of July to September, 2013 to find out the prevalence and clinico-pathological findings of Peste des petits ruminants (PPR) in goats, and to observe the response of PPR-goats to different treatments. During the course of study 202 goats were examined of which 98 were PPR positive. Diagnosis of a PPR case was made following the clinical examinations. The results showes that the median age of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
2
3
0
Order By: Relevance
“…The heart rate, pulse rate and respiratory rate were also high, deferring from the normal reference values reported by Jackson and Cockcroft (34), Radostits et al, (35), but this occurrence agrees with the report by Naznin et al (37), who reported that the heart rate, pulse rate and respiratory rate in PPR affected goats are high. It could be postulated, also, that the significant increase in the respiratory rate was due to harsh environmental and weather conditions as well as the presence of the virus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The heart rate, pulse rate and respiratory rate were also high, deferring from the normal reference values reported by Jackson and Cockcroft (34), Radostits et al, (35), but this occurrence agrees with the report by Naznin et al (37), who reported that the heart rate, pulse rate and respiratory rate in PPR affected goats are high. It could be postulated, also, that the significant increase in the respiratory rate was due to harsh environmental and weather conditions as well as the presence of the virus.…”
Section: Discussionsupporting
confidence: 90%
“…Naznin et al (37) reported that the recovery rate from clinical signs was higher in goats treated with parenteral administration of oxytetracycline but as seen in the findings of this work, it was observed that the combined therapy using Acyclovir, Oxytetracycline and Ivermectin, had a better efficacy than the other groups treated singly. The recovery rate of the combined therapy and the single-Oxytetracycline treated groups were comparable one week post-treatment.…”
Section: Discussionsupporting
confidence: 40%
“…The incubation period of the disease is 4–6 days, but can be up to 14 days. Clinical infection varies, and may include fever, oculo‐nasal discharges, oral erosions, pneumonia and diarrhoea (Naznin, Ahaduzzaman, Chowdhury, & Biswas, 2014). The infection period is usually 5–7 days, and death of the infected animal may occur within 10–12 days post‐infection due to severe dehydration and respiratory failure (Diallo et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…As initial search results showed 344 workable scientific papers which was downed to 92 after deletion of duplicate papers. There were 39 papers selected after screening of the papers showed in the Figure 1 and among them 34 were particularly on goat (Islam et al, 2013;Karim et al, 2014;Rahman et al, 2012;Kabir et al, 2010;Rahman et al, 2011;Sardar et al, 2006;Sarker et al, 2011;Noman et al, 2011;Alam et al, 2015;Nath et al, 2014;Rabbi et al, 2014;Lucky et al, 2016;Naznin et al, 2016;Parvez, 2014;Rakshit et al, 2015;Siddiqui et al, 2016;Sarker et al, 2015;Ahmed et al, 2017;Alam et al, 2018;Amin, 2016;Bueaza, 2015;Debnath et al, 2015;Mohanto et al, 2018;Khan et al, 2018;Md. Mustafizur Rahaman, 2017;Meher et al, 2017;Sadar et al, 2018;Yousuf et al, 2017), 4 papers dealing on both sheep and goat (Hasan et al, 2012;Mondal et al, 2014;Banik et al, 2008) a single article particularly on sheep (Chowdhury, 2011).…”
Section: Search Results and Eligible Studiesmentioning
confidence: 99%